2014
DOI: 10.4161/19420862.2014.976431
|View full text |Cite
|
Sign up to set email alerts
|

First human study of a chimeric anti-methamphetamine monoclonal antibody in healthy volunteers

Abstract: This first-in-human study examined the safety and pharmacokinetics of ch-mAb7F9, an anti-methamphetamine monoclonal antibody, in healthy volunteers. Single, escalating doses of ch-mAb7F9 over the range of 0.2 to 20 mg/kg were administered to 42 subjects who were followed for 147 d. Safety was measured by physical examinations, adverse events, vital signs, electrocardiograms, and clinical laboratory testing. Serum ch-mAb7F9 concentration and immunogenicity analyses were performed. There were no serious adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…This includes anti-drug monoclonal antibodies (mAbs), which are hypothesized to bind to these drugs of abuse and prevent their entry into the brain, thus nullifying the central nervous system (CNS) effects of these drugs. This approach has shown success in preclinical animal studies of an anti-methamphetamine mAb [2], which has advanced into clinical trials [3]. A hybridoma-derived anti-cocaine mAb with a human heavy chain and a murine light chain (designated 2E2) and the reengineered recombinant version of this anti-cocaine mAb, designated h2E2, have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…This includes anti-drug monoclonal antibodies (mAbs), which are hypothesized to bind to these drugs of abuse and prevent their entry into the brain, thus nullifying the central nervous system (CNS) effects of these drugs. This approach has shown success in preclinical animal studies of an anti-methamphetamine mAb [2], which has advanced into clinical trials [3]. A hybridoma-derived anti-cocaine mAb with a human heavy chain and a murine light chain (designated 2E2) and the reengineered recombinant version of this anti-cocaine mAb, designated h2E2, have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Since the main predictor of success of cocaine vaccines is the amount of antibody raised, injection of known doses of a high-affinity anti-cocaine monoclonal antibody (mAb) should provide a more consistent and reliable therapeutic effect. An anti-methamphetamine mAb has shown effectiveness in animal models of methamphetamine abuse (Laurenzana et al, 2003) and has advanced into clinical trials (Stevens et al, 2014). A chimeric anti-cocaine mAb 2E2 has been effective in decreasing cocaine concentrations in the brain in mice (Norman et al, 2007) and has raised the cocaine priming threshold in rats (Norman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of anti-drug mAb is a strategy for treating drug dependence or overdose that has shown pre-clinical proof of efficacy against nicotine, 137,138 cocaine, [139][140][141] phencyclidine, 142 methamphetamine, 143 and heroin. 144,145 The first human study of the anti-methamphetamine chimeric mAb7F9, 0.2-20 mg/kg i.v., showed safety (NCT01603147, 146 The authors also detected anti-mAb auto-Ab, a sign of immunogenicity, in 4 out of 32 subjects, but concluded that more studies were needed to understand their biological relevance or their impact on the function of anti-methamphetamine mAb. 146 To facilitate FDA approval, it will be useful to characterize recombinant humanized anti-drug mAb for presence of post-translational modifications, resulting in protein heterogeneity, that may potentially affect in vivo efficacy.…”
Section: Other Biologics For Sudmentioning
confidence: 99%
“…144,145 The first human study of the anti-methamphetamine chimeric mAb7F9, 0.2-20 mg/kg i.v., showed safety (NCT01603147, 146 The authors also detected anti-mAb auto-Ab, a sign of immunogenicity, in 4 out of 32 subjects, but concluded that more studies were needed to understand their biological relevance or their impact on the function of anti-methamphetamine mAb. 146 To facilitate FDA approval, it will be useful to characterize recombinant humanized anti-drug mAb for presence of post-translational modifications, resulting in protein heterogeneity, that may potentially affect in vivo efficacy. 147 Although clinical data show promise for mAb-based therapy for SUD, long-term treatment of SUD will require multiple mAb doses throughout the entire course of therapy and may still be limited by cost.…”
Section: Other Biologics For Sudmentioning
confidence: 99%